Akt Inhibition Is Associated With Favorable Immune Profile Changes Within the Tumor Microenvironment of Hormone Receptor Positive, HER2 Negative Breast Cancer - Marks, Douglas K. (Front Oncol, 2020)
Background: The PI3K/Akt/mTOR pathway in part impacts tumorigenesis through modulation of host immune activity. To assess the effects of Akt inhibition on the tumor micro-environment (TME), we analyzed tumor tissue from patients with operable hormone receptor positive, HER2 negative breast cancer (BC) treated on a presurgical trial with the Akt inhibitor MK-2206. Methods: Quantitative multiplex immunofluorescence (qmIF) was performed using CD3, CD8, CD4, FOXP3, CD68, and pancytokeratin on biopsy and surgical specimens of MK-2206 and untreated, control patients. nanoString was performed on surgical specimens to assess mRNA expression from MK-2206-treated vs. control patients. Results: Increased CD3+CD8+ density was observed in post vs. pre-treatment tissue in the MK-2206-treated vs. control patients (87 vs. 0.2%, p < 0.05). MK-2206 was associated with greater expression of interferon signaling genes (e.g., IFI6, p < 0.05) and lower expression of myeloid genes (CD163, p < 0.05) on differential expression and gene set enrichment analyses. Greater expression of pro-apoptotic genes (e.g., BAD) were associated with MK-2206 treatment (p < 0.05). Conclusion: Akt inhibition in operable BC was associated with a favorable immune profile in the TME, including increased CD3+CD8+ density and greater expression of interferon genes. Additional studies are warranted, as this may provide rationale for combining Akt inhibition with immunotherapy.